Integration Of Design For Modularity And Design For Assembly To Enhance Product Maintainability. - Abdullah, Ahmad Baharuddin; Yusoff, M. S.; Mohd Ripin, Zaidi (2006)
This paper discussed the relationship between design for modularity and maintenance in order to extend product life. Modularization can be described as an engineering approach to simplify component or product configuration as functional independence it creates.